Utilization of Pop-Up Book to Increase Vocabulary and Learning Motivation of Junior High School Students - Nabila Aslam; Mardiah, Henny (CERED Indonesia, 2024)
The main objective of this study is to determine the effect of utilization of pop-up book to increase vocabulary and learning motivation of junior high school students. The study was conducted at SMP Bina Taruna, Jl. Paya Pasir, Marelan, Medan City, North Sumatera. The population in this study was 8th grade students, consisting of 3 classes with total of 90 students of two classes. This study used quantitative method with quasi-experimental design by applying purposive sampling. The results of this study have represented to have an impact on students’ vocabulary and learning motivation. The effect of the utilizing of pop-up book can be seen on pre-test and post-test averages in the experimental class that is from 30.07 to 75.65. Other evidence, as shown in the results of the t-test analysis, findings and discussion, the results show that the paired sample test is 14.694 and t-table is 2.052 with a significance value (2-tailed) is <001, it means less than 005. Then, the lowest students learning motivation score is 76 and the highest score is 100. So, they were categorized as high and very high learning motivation. Therefore, Ha was recognized. Thus, it can be concluded the utilization of pop-up book affects to improve vocabulary and learning motivation of junior high school students.